Unusual Transalveolar and Transmuco-Gingival Root Avulsion of a Fractured Primary Central Incisor: A Case with an 8-Year Follow-Up - Ferrés-Amat, E. (Case Rep Dent, 2015)
The purpose of this unique case report is to describe a very unusual dentoalveolar fracture associated with avulsion of the near-complete root. A 3-year-old male patient came for consultation after a dentoalveolar trauma with a “fragment that looks like canine” found in his mouth by his mother. This boy suffered root fracture of the upper primary central right incisor, accompanied by transalveolar and transmuco-gingival avulsion of the tooth root fragment, leaving the crown in its position in the dental arch. Clinical and radiological examinations were performed in order to follow up the case: 15 days, one month, and three months after trauma, the crown had a slight mobility without other clinical or radiological signs. After six months, the upper primary central right incisor's crown was exfoliated. Open bite due to the persistence of the pacifier habit favored the crown retention in the mouth. This case emphasizes the importance of primary diagnosis and follow-up of trauma cases. To the best of our knowledge, this kind of dental injury has not been previously described in the literature nor in the current Dental Trauma guidelines for the management of traumatic dental injuries in the primary dentition.